THU0098 WHICH FACTORS INFLUENCE ACHIEVEMENT OF TREATMENT SATISFACTION IN RHEUMATOID ARTHRITIS?. (June 2019) - Schaefer, Martin; Kekow, Jörn; Rockwitz, Karin; Liebhaber, Anke; Zink, Angela; Strangfeld, Anja
Abstract : Background: The satisfaction of RA patients with their pharmacological therapy is a relevant patient reported outcome which influences treatment adherence and continuation. However, it has not been investigated frequently, and almost never in large studies. Objectives: To assess factors exerting a potential influence on the satisfaction with the pharmacological treatment and to quantify this influence. Methods: The German register RABBIT is a prospective longitudinally followed cohort of RA patients enrolled with a new start of a DMARD after at least one csDMARD failure. This analysis comprises patients who were enrolled with start of a DMARD between 01/2009 and 04/2018, who were observed for at least 12 months and had been on the therapy prescribed at enrolment for at least six months. Satisfaction with the applied treatment was measured in four categories from "very satisfied" to "very unsatisfied". Logistic regression combined with multiple imputation of missing values was performed to calculate odds ratios (ORs) for factors which might have an influence on treatment satisfaction. Results: At treatment onset, 55% of the 8, 177 patients were "very" or "rather" satisfied (in the following: "satisfied"), while the rest was "very" or "rather" unsatisfied (in the following: "unsatisfied") with their therapy. After one year of treatment, 86% of patients were satisfied with their treatment. Factors with positive impact on whether patients reached the target of treatment satisfaction were satisfaction at baseline, reduction of DAS28-BSG, pain and glucocorticoid dose as well as the increase of physical function. Depression, obesity as well as a prior treatment failure of bDMARDs had a negative influence on the outcome (see Table 1 ). The DAS28 component most influential on treatment satisfaction was the patient global health assessment. Regarding glucocorticoid therapy, being still treated with either 5 to 15 mg (OR: 0.66, 95% CI: 0.55; 0.79) or ≥ 15 mg glucocorticoids (OR: 0.25, 95% CI: 0.15; 0.41) had a negative impact on the achievement of therapy satisfaction (data not shown). Conclusion: Reductions in disease activity, pain and glucocorticoid dosage as well as improvement of physical function increase the chance to achieve treatment satisfaction. On the other hand, depression and obesity as well as prior treatment failures with bDMARDs are obstacles to therapy satisfaction. For physicians, these results suggest that efforts to taper glucocorticoid doses are worthwhile to improve patient's satisfaction. Acknowledgement: Disclosure: RABBIT is supported by a joint, unconditional grant from AbbVie, Bristol-Myers Squibb, Celltrion, Hexal, Lilly, MSD Sharp & Dohme, Pfizer, Roche, Samsung Bioepis, Sanofi-Aventis, and UCB. Disclosure of Interests: Martin Schaefer: None declared, Jörn Kekow: None declared, Karin Rockwitz: None declared, Anke Liebhaber: None declared, Angela Zink Speakers bureau: Speakers fees from AbbVie, Janssen, Pfizer, Roche, Sanofi, Anja Strangfeld Speakers bureau: Speakers fees from Bristol-Myers Squibb, MSD, Pfizer, Roche